A hysteresis energy dissipation based model for multiple loading damage in continuous fiber-reinforced ceramic-matrix composites. (1st April 2019) - Longbiao, Li
Abstract: In this paper, a hysteresis energy dissipation based damage model for fiber-reinforced ceramic-matrix composites (CMCs) subjected to multiple loading stress levels is developed. Considering the combination effects of multiple loading sequences and multiple fatigue damage mechanisms, i.e., matrix cracking, fiber/matrix interface debonding and interface wear, the evolution of the fiber/matrix interface debonding and sliding, fatigue hysteresis loops, fatigue hysteresis dissipated energy and fatigue hysteresis modulus changing with increasing applied cycles are analyzed. The effects of fiber volume fraction, matrix crack spacing, fatigue peak stress and fatigue stress range on the damage development inside of CMCs are discussed. The difference of the fiber/matrix interface shear stress existed between the interface wear region and new interface debonded region affects the fiber/matrix interface debonded length and loading carrying ability of intact and broken fibers. The damage evolution for C/SiC and SiC/SiC composites subjected to multiple fatigue loading sequences are predicted using the hysteresis energy dissipation damage model. Under multiple loading stress, the fatigue hysteresis dissipated energy increases when high peak stress and stress range increases due to the increase of fiber/matrix interface sliding range. However, when the low peak stress increases, the evolution of fatigue hysteresis dissipated energy depends on the interface debonding and sliding state. Graphical abstract: Image 1 Highlights: Multiple loading fatigue damage of fiber-reinforced ceramic-matrix composites (CMCs) is investigated. A hysteresis energy dissipation based damage model is developed. The influences of fiber volume fraction, matrix crack spacing, fatigue peak stress and fatigue stress range are discussed. The developed hysteresis damage model is validated.